Grappling with compounding crises in domestic fertilizer markets in Africa: The case of Ethiopia - Abay, Kibrom A.; Assefa, Thomas; Berhane, Guush; Abate, Gashaw T.; Hebebrand, Charlotte (International Food Policy Research Institute, 2024)
Global fertilizer markets experienced significant price surges beginning in 2020 and through 2022 due to a combination of factors, including higher natural gas prices, supply chain disruptions triggered by COVID-19, trade disruptions due to the Russia-Ukraine war, and export restrictions. Although parallel increases in international agricultural commodity prices may have cushioned these price shocks, insufficient availability and affordability of fertilizers are likely to have affected yield and profitability of smallholder production systems. Whereas international prices have come down from their peaks, many countries continue to grapple with persistent inflation, deteriorating terms of trade, and macroeconomic imbalances, which are keeping domestic fertilizer prices high. While these impacts may vary by country depending on fertilizer availability and farm households’ purchasing power, smallholder farmers are likely to face the brunt of these challenges given the already limited access to fertilizer markets and resources, including in the focus country of this post, Ethiopia.